MINIMAX PRINCIPLE IN THEORY AND PRACTICE OF MODERN GRAIN COMBINE ACTUATOR OPTIMAL DESIGN - Victor V. Radin (Advanced Engineering Research)
The problem on the design values optimal choice of the grain combine drive elements, when these elem ents are implemented through the V - belt and hydraulic transmissions, is set and solv ed. For this purpose the minimax pri nciple, implemented through the method of the optimal design of the state - space dynamic system parameters under the alternating loads, is used. The author’s previously generated theoretical model of the combine d rive dyn amic system with the nonlinear nonholonomic first - order constraint is used to form the state space.